Pengaruh Customer Relationship Marketing (CRM) Dan Kepuasan Konsumen Terhadap Loyalitas Konsumen Di Dealer Ahass Aries Putra Bandung Kabupaten Tulungagung - Duriatin Koni’ah; Anwar Bowo Leksono; Edy Murdiyanto (CV. Aksara Global Akademia, 2023)
In the current era of globalization, companies are required to improve services professionally in accordance with their respective fields. This study aims to determine the effect of customer relationship marketing (CRM) and consumer satisfaction on consumer loyalty at Ahass Aries Putra Dealer Bandung, Tulungagung Regency. The variables of this study are customer relationship marketing, satisfaction and loyalty. The location of this study exists on Jalan Panglima Sudirman No. 125, Genengan, Bandung, Tulungagung Regency. This type of research uses a descriptive quantitative type. The sample in this study used purposive sampling techniques which resulted in a total of 197 respondents. The analysis tool used for this study is SPSS For Windows 25. Based on tests conducted with multiple linear regression analysis, the t test shows that customer relationship marketing has a partial influence on consumer loyalty. This is shown from the value of 3.596 > from 1.97227 then, consumer satisfaction also has a partial effect on consumer loyalty as seen from the value of 11.777 > from 1.97227. Test F shows that the variables customer relationship marketing and customer satisfaction simultaneously affect consumer loyalty seen from the value of 104.22 > 1.97227.